Thoracic aortic aneurysm. An experimental model in pigs - Argenta,Rodrigo (2021)
ABSTRACT Purpose To describe an unpublished experimental model of descending thoracic aortic aneurysm in pigs. Methods Ten Landrace female pigs aged 10 to 12 weeks old and with initial weights from 17 to 25 kg were anesthetized and their descending thoracic aortas exposed by fifth intercostal space left thoracotomy. The thoracic aorta was isolated. A 2-cm wide × 2-cm long patch of ready-made bovine pericardium was sewn onto the left anterolateral side of the aorta. After three weeks’ follow-up, a control aortography was taken, and the animals were euthanized. The segment of thoracic aorta containing the aneurysm and the adherent tissues were explanted en bloc. The specimens were stained for histological examination. Results One hundred percent of the animals survived the procedure, and after sacrifice a patent aneurysm was observed in all of them. There were no defects on the suture lines. Weight gain during follow-up was normal. All specimens exhibited intense adventitial reaction with myofibroblasts. There were no complications related to the thoracotomy. Conclusions The descending thoracic aortic aneurysms induced experimentally appear to be stable, were of easy execution, with null mortality and no influence on the animals’ normal development. Furthermore, they have similar characteristics to those observed in human degenerative aneurysms.